Nottingham Express Transit: The role of green innovation in the drive for sustainable mobility through improved public transport. (February 2018) - Disney, John; Rossiter, Will; Smith, David J
Traffic congestion at peak times has long been a problem facing cities in the United Kingdom. 1 Latterly concern about combating congestion has been hightened by worries over carbon emissions and poor air quality. In tackling these problems, green innovations incorporating new technologies appear to have much to offer, although progress in implementing these sorts of innovation appears to have been slow. This case study analyses the efforts of one city to tackle these problems by pioneering a number of green innovations including the introduction of a light rail system employing trams known as Nottingham Express Transit as well as electric and gas-powered buses. The nature of these innovations is explored together with a detailed examination of how they came to be implemented and the impact they have had.